Vitrum Osteomag and calcium carbonate efficacy comparative assessment in patients with rheumatoid arthritis receiving glucocorticoids - I S Dydykina; Y. V. Muravyov (Научно-практическая ревматология, 2004)
Objective, To study efficacy and safety of Vitrum Osteomag (VO) in prophylaxis of osteoporosis in pts with rheumatoid arthritis (RA) during 12 months. Material and Methods. 50 female with osteopenia confirmed with densitometry were included aged 50 to 70 years in the menopause for more than 2 years receiving small doses of glucocorticoids (<15 mg/day). In an open randomized comparative study of efficacy and safety of VO was administered to 25 pts per os a tablet twice a day and 25 pts received calcium carbonate powder 1000 mg/day for prophylaxis of steroid osteoporosis in RA pts consuming normal quantity of calcium with food. Results. After one year of therapy in pts treated with VO lumbar and femoral BMD was significantly higher than in those receiving calcium carbonate. Tolerability of the drug was good. Conclusion. VO stabilizes BMD in postmenopausal RA pts receiving glucocorticoid therapy and may be included in complex therapy for prophylaxis of steroid osteoporosis.